ALDH1A3 correlates with luminal phenotype in prostate cancer. Issue 4 (April 2017) - Wang, Shangqian; Liang, Chao; Bao, Meiling; Li, Xiao; Zhang, Lei; Li, Shuang; Qin, Chao; Shao, Pengfei; Li, Jie; Hua, Lixin; Wang, Zengjun
Prostate cancer is the most common male malignancies in the United States. The specific characteristics of different disease stages have been deeply investigated. We present our data on ALDH1A3 as a potential therapeutic target for the prostate cancer based on several functional investigations. Also, we used The Cancer Genome Atlas datasets for primary prostate cancer to detect the relevance of ALDH1A3 and prostate cancer luminal phenotype. We found that ALDH1A3 correlated with androgen receptor signaling pathway in primary prostate cancer, which is consistent with its luminal layer localization. Then, from the genetic manipulation assay, we knocked out the ALDH1A3 in PC-3 cells and found significantly reduced proliferation rate as well as the invasion ability. Furthermore, we looked up our single center primary prostate cancer post-operative follow-up data and suggested that the high level ALDH1A3 expression could predict the poor progression-free survival in a 158-patient cohort. We concluded that ALDH1A3, localized in luminal layer in prostate epithelium, is highly expressed in prostate cancer. It played important role in maintaining the proliferation, invasion, and cell cycle. It can also become the potential biomarker in the future to guide the therapeutic manipulations for primary prostate cancer.